Clinical applicability survey of the Clinical Pathway for Short Stature (2019 Edition) - XIAO Linqi; FENG Jiajia; PAN Hui; LUO Xiaoping; GONG Chunxiu; ZHANG Pan; ZHANG Yu; HAN Yong; LIN Likai (Yixue xinzhi zazhi)
Objective To investigate the clinical applicability of the Clinical Pathway for Short Stature (2019 Edition). Methods A cross-sectional survey was conducted among pediatric endocrinologists using a questionnaire adapted from the guideline clinical applicability evaluation tool. Descriptive analysis was performed on the basic characteristics of respondents, dimensional scores, pathways of access, and factors influencing implementation. Kruskal-Wallis rank-sum test and Nemenyi test were used for multiple and pairwise comparisons. Multiple linear regression analysis combined with stepwise regression was used to analyze factors influencing the scores. Results A total of 206 valid questionnaires were collected. The mean and median scores for all dimensions and overall evaluation of the clinical pathway for short stature were ≤75 points. The median scores for acceptability, readability, feasibility, accessibility, and overall evaluation were 75.00, 62.50, 62.50, 50.00, and 75.00, respectively. Eighteen percent of the survey respondents believed that there were implementation barriers to the clinical pathway, including factors related to medical staff, patients, the environment, and the clinical pathway itself. Multiple comparisons and multiple linear regression analysis showed that familiarity with the clinical pathway was the main influencing factor for the scores (P